Biological treatment of sewage treatment plant sludge by pure bacterial culture with optimum process conditions in a stirred tank bioreactor - Alam, Md. Zahangir; Muyibi , Suleyman Arebu; Jamal, Parveen (2007)
Biological treatment of sewage treatment plant (STP) sludge by potential pure bacterial culture (Bacillus sp.) with optimum process conditions for effective biodegradation and bioseparation was carried out in the laboratory. The effective and efficient bioconversion was evaluated with the treatment of pure bacterial culture and existing microbes (uninnoculated) in sludge. The optimum process conditions i.e., temperature, 40◦C; pH, 6; inoculum, 5% (v/v); aeration, 1 vvm; agitation speed, 50 rpm obtained from the previous studies with chemical oxygen demand COD at 30 mgL−1 were applied for the biological treatment of sludge. The results indicated that pure bacterial culture (Bacillus sp.) showed higher degradation and separation of treated sludge compared to treatment with the existing mixed microbes in a stirred tank bioreactor. The treated STP sludge by potential pure bacterial culture and existing microbes gave 30% and 11%; 91.2% and 59.1; 88.5% and 52.3%; 98.4% and 51.3%; 96.1% and 75.2%; 99.4% and 72.8% reduction of total suspended solids (TSS, biosolids), COD, soluble protein, turbidity, total dissolved solids (TDS) and specific resistance to filtration (SRF), respectively within 7 days of treatment. The pH was observed at 6.5 and 4 during the treatment of sludge by pure culture and existing microbes, respectively.